2005
DOI: 10.1128/mcb.25.20.8874-8886.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin Is Required for DNA Integrity and p19Arf Protein Stability

Abstract: Nucleophosmin (NPM) is a nucleolar phosphoprotein that binds the tumor suppressors p53 and p19Arf and is thought to be indispensable for ribogenesis, cell proliferation, and survival after DNA damage. The NPM gene is the most frequent target of genetic alterations in leukemias and lymphomas, though its role in tumorigenesis is unknown. We report here the first characterization of a mouse NPM knockout strain. Lack of NPM expression results in accumulation of DNA damage, activation of p53, widespread apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
210
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(226 citation statements)
references
References 44 publications
12
210
1
3
Order By: Relevance
“…These reciprocal antagonistic signals eliminate the cellular fail-safe mechanisms induced by oncogenes, namely Arf/p53 activation and senescence, unleashing the oncogenic potential of E1A and NPMc þ . Since NPM is required for Arf stability (Colombo et al, 2005), our data suggest two possibilities for the dominant-negative action of NPMc þ on Arf: NPMc þ delocalizes NPM to the cytoplasm, thus attenuating NPM's protective role on Arf (den Besten et al, 2005), or NPMc þ directly delocalizes Arf to the cytoplasm and destabilizes it (Colombo et al, 2006). Our data showed that the endogenous NPM was only partially delocalized by NPMc þ (Figure 1a), therefore supporting the second hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…These reciprocal antagonistic signals eliminate the cellular fail-safe mechanisms induced by oncogenes, namely Arf/p53 activation and senescence, unleashing the oncogenic potential of E1A and NPMc þ . Since NPM is required for Arf stability (Colombo et al, 2005), our data suggest two possibilities for the dominant-negative action of NPMc þ on Arf: NPMc þ delocalizes NPM to the cytoplasm, thus attenuating NPM's protective role on Arf (den Besten et al, 2005), or NPMc þ directly delocalizes Arf to the cytoplasm and destabilizes it (Colombo et al, 2006). Our data showed that the endogenous NPM was only partially delocalized by NPMc þ (Figure 1a), therefore supporting the second hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…NPM Ϫ/Ϫ primary fibroblasts (mouse embryonic fibroblasts) show centrosome amplification, polyploidy, activation of p53, growth arrest, and senescence. 24,46 More importantly, NPM haploinsufficiency in NPM ϩ/Ϫ mouse embryonic fibroblasts that mimic cancer cells harboring chromosomal rearrangements/deletions at the NPM1 locus show an immortal phenotype with noticeably high proliferation rates. 47 Furthermore, in the p53 Ϫ/Ϫ background, NPM ϩ/Ϫ mouse embryonic fibroblasts have higher proliferation rates than NPM ϩ/ϩ mouse embryonic fibroblasts, and they are more susceptible to transformation by activated oncogenes, indicating that loss of one Npm1 allele cooperates with oncogenes in transformation and tumorigenesis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, in the p53 Ϫ/Ϫ background, NPM ϩ/Ϫ mouse embryonic fibroblasts have higher proliferation rates than NPM ϩ/ϩ mouse embryonic fibroblasts, and they are more susceptible to transformation by activated oncogenes, indicating that loss of one Npm1 allele cooperates with oncogenes in transformation and tumorigenesis both in vitro and in vivo. 46 Npm1 ϩ/Ϫ mice show higher susceptibility for development of malignancies, especially of hematological and lymphoid origin, than their wild-type counterparts, indicating NPM as a haploinsufficient tumor suppressor. 29 Here we show that reduced NPM protein expression was associated with poor prognosis and that over-expression of NPM in the MDA-MB-231 breast cancer cells abrogated their growth in soft agar, supporting a tumor suppressive function for NPM in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we have shown NSC348884 to induce apoptosis in several types of cancer cells even in the absence of other stressful events (Figure 4). A mouse NPM knockout experiment demonstrated that lack of NPM expression results in accumulation of DNA damage (Colombo et al, 2005). Apoptosis induced by NSC348884 may be involved in mediating increased DNA damage.…”
Section: Apoptosis Induction By Npm Inhibitor Nsc348884 W Qi Et Almentioning
confidence: 99%